Giant increase in piezoelectric coefficient of AlN by Mg-Nb simultaneous addition and multiple chemical states of Nb - Uehara, Masato; Shigemoto, Hokuto; Fujio, Yuki; Nagase, Toshimi; Aida, Yasuhiro; Umeda, Keiichi; Akiyama, Morito (Applied physics letters, 2017)
Aluminum nitride (AlN) is one of piezoelectric materials, which are eagerly anticipated for use in microelectromechanical systems (MEMS) applications such as communication resonators, sensors, and energy harvesters. AlN is particularly excellent in generated voltage characteristics for the MEMS rather than oxide piezoelectric materials such as lead zirconium titanate Pb(Zr, Ti)O3. However, it is necessary to improve the piezoelectric properties of AlN in order to advance the performance of the MEMS. We dramatically increased the piezoelectric coefficient d 33 of AlN films by simultaneously adding magnesium (Mg) and niobium (Nb). The d 33 of Mg39.3Nb25.0Al35.7N is 22 pC/N, which is about four times that of AlN. The d 33 is increased by Mg and Nb simultaneous addition, and is not increased by Mg or Nb single addition. Interestingly, the Nb has multiple chemical states, and which are influenced by the Mg concentration.